Antibiotics in soil and water in China–a systematic review and source analysis - Lyu, Jia; Yang, Linsheng; Zhang, Lan; Ye, Bixiong; Wang, Li (Environmental pollution (1987), 2020)
With the high production and consumption of antibiotics in recent years due to increasing economic development and improving population health, China is facing serious antibiotic pollution in the environment, and it is becoming a significant threat to ecology and human health. This study explores the spatial distribution patterns of 65 antibiotics in soil, surface water and coastal water based on a systematic review. Potential emission sources of antibiotics are also analyzed using data extracted from the reviewed literature. The results suggest that China has very high antibiotic detection rates of 100%, 98.0% and 96.4% for soil, surface water and coastal water, respectively. Regions with high antibiotic levels are mainly located in Bohai Bay, including the Beijing‒Tianjin‒Hebei region, Liaoning and Shandong Provinces, and Yangtze River. Tetracyclines (TCs) and quinolones (QNs) are the dominant antibiotics observed in soil and are mainly attributed to the use of manure as fertilizer and the reuse of domestic wastewater. Sulfonamides (SAs), macrolides (MLs), TCs and QNs are the dominant antibiotics observed in surface water and are mainly attributed to aquaculture and the emission of domestic sewage. QNs are the dominant antibiotics observed in coastal water and are mainly attributed to marine cultivation. The detection frequencies and concentrations of TCs, QNs, SAs and MLs in both soil and water are much higher than those in other developed countries. Suggestions including restricting antibiotic usages in livestock farming and aquaculture, innovation of wastewater treatment technology to improve antibiotic removal rate, and establishing guidelines on antibiotic concentration for wastewater discharge and organic fertilizer are provided. [Display omitted] •China has very high antibiotic detection rates for soil and aquatic environment.•Tetracyclines and quinolones were the dominant antibiotics in soil.•Antibiotic residues in soil were mainly from fertilizer and domestic wastewater.•Surface water had complex compositions of antibiotic residues.•Antibiotic pollution in aquatic environment were mainly attributed to aquaculture. China has very high antibiotic detection rates for environments. Management of antibiotic exposure from environments should be given high public health priority.